The efficacy and safety of aflibercept and conbercept in diabetic macular edema - Cai S; Yang Q; Li X; Zhang Y (Dove Medical Press, 2018)
Siwei Cai, Qianhui Yang, Xiaorong Li, Yan Zhang Tianjin Medical University Eye Hospital, Tianjin Medical University Eye Institute, College of Optometry and Ophthalmology, Tianjin Medical University, Tianjin 300384, People’s Republic of China Abstract: Diabetic macular edema (DME) has shown an increasing prevalence during the past years and is the leading cause of diabetic retinopathy blindness. Traditional treatment modalities include laser and corticosteroid therapy, which, however, either act through unclear mechanisms or cause cataracts and elevated intraocular pressure. In recent years, as the pathogenic role of VEGF in DME has been well-recognized, the intravitreal injection of anti-VEGF drugs has become the first-line treatment of DME due to their great efficacy in improving visual acuity and mitigating macular edema. Advantages have been shown for aflibercept and conbercept, the two recombinant decoy receptors that can bind VEGF with high specificity and affinity, in DME treatment in clinical trials conducted both worldwide and in People’s Republic of China. This review introduces the structural characteristics and molecular mechanisms of action of these two anti-VEGF drugs, and summarizes the clinical trials evaluating their efficacy and safety, with the hope to provide clues for designing optimal and personalized therapeutic regimens for DME patients. Keywords: diabetes, diabetic retinopathy, diabetic macular edema, therapy, aflibercept, conbercept, clinical trial, VEGF decoy receptor